2017
DOI: 10.1063/1.4991202
|View full text |Cite
|
Sign up to set email alerts
|

Physiology response of the indigenous cattle breeds to the environment in West Sumbawa, Indonesia

Abstract: Morphometric study of mantis shrimp Harpiosquilla harpax (De Haan, 1844) Corresponding author: alaksono@sci.ui.ac.id Abstract. Heat stress in cattle welfare is a growing concern because of increase in ambient temperature due to global warming. Physiological adaptation is as a way to survive and reproduce by regulation internal body temperature. West Sumbawa is a dry tropic area in eastern Indonesia where its temperature range is 24-38 °C and relative humidity is 50-90 %. This study aimed to determine the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Similarly, in a comparative study by Ashutosh et al (2000) identified that the RR and RT are higher in Avivastra sheep than Chokla sheep breed during heat stress exposure. In another recent study, Aritonang et al (2017) compared the adaptive capacity of Bali cattle with Sumbawa Ongole cattle and observed that Bali cattle relied much on RT while Ongole cattle relied on the respiration rate to maintain the thermal balance. Further, Gir cattle breed was the breed least adapted while the Sindhi and Girolando breeds showed the best physiological response to thermal stress (Cardoso et al 2015).…”
Section: Breed Differences In Physiological Adaptability In Livestockmentioning
confidence: 99%
“…Similarly, in a comparative study by Ashutosh et al (2000) identified that the RR and RT are higher in Avivastra sheep than Chokla sheep breed during heat stress exposure. In another recent study, Aritonang et al (2017) compared the adaptive capacity of Bali cattle with Sumbawa Ongole cattle and observed that Bali cattle relied much on RT while Ongole cattle relied on the respiration rate to maintain the thermal balance. Further, Gir cattle breed was the breed least adapted while the Sindhi and Girolando breeds showed the best physiological response to thermal stress (Cardoso et al 2015).…”
Section: Breed Differences In Physiological Adaptability In Livestockmentioning
confidence: 99%
“…In Brazil, Sindhi and Girolando breeds showed better physiological response to thermal stress than Gir cattle [10]. Increase in respiration rate was reported in Nellore breed when exposed to heat load [11].…”
Section: Introductionmentioning
confidence: 91%
“…Sahiwal cows better regulate body temperature in response to heat stress than Karan Fries 8 . It was observed that Ongole cattle rely on the respiration rate to maintain thermal balance, while, Bali cattle rely on rectal temperature 12 . In Brazil, Sindhi and Girolando breeds showed better physiological response to thermal stress than Gir cattle 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Apabila dibandingkan dengan penelitian lain, hasil tersebut masih berada di dalam kisaran sapi sehat. Aritonang et al (2017) Walaupun ada kecenderungan perbedaan frekuensi nafas antara sapi kontrol dan perlakuan, serta dari hari ke 3 ke hari ke 38 dan 66, tetapi secara fisik semua sapi dalam kondisi yang sehat. Perbedaan ini kemungkinan disebabkan oleh faktor lingkungan pada saat pemeriksaan, terutama suhu lingkungan yang tidak sama antara hari ke 3, 38 dan 66 pasca beranak.…”
Section: Hasil Dan Pembahasanunclassified